(untitled) (Medical Forum Monthly, 2024)
Objective: The aim of our study is to see the effect of controlled diabetes done preoperatively as well as postoperatively done so that the fear of complications in minds of diabetic patients should be removed. Study Design: Cross sectional study Place and Duration of Study: This study was conducted at Surgical department, PMCH Nawabshah from June 2016 to June 2018. Materials and Methods: This study included patients suffering from Diabetes Mellitus and also diagnosed diabetes after admission in surgical wards. They were admitted electively through OPD and blood sugar along with HbA1c was obtained in order to commence the treatment of D.M. The patients were shifted from oral anti-hyperglycemic drugs to insulin used subcutaneously or intravenous. Only the patients with controlled diabetes were operated and outcome was assessed. Results: This is a study of 110 patients. Of 110, 85 (77.27%) were already diagnosed diabetic patients under oral therapy and 25(22.72%) were labeled as diabetic during preoperative preparation of the patients. They were operated for different surgical procedures for multiple elective cases diseases like inguinal hernia, Ventral hernias, Goiter, hemorrhoids, chronic fissure in ano, low type fistula in ano, laparoscopic/open cholycystectomy and for colonic masses. Postoperatively, the blood sugar level of all patients were acurately assessed and monitored and outcomes were observed. 20 (18.18%) patients developed infected wounds, 10(9.09%) went into Paralytic Ileus, 3(2.72%) presented with subcutaneous Hematoma, 1 (0.9%) was readmitted with burst abdomen and 1 (0.9%) developed sepsis. All were treated accordingly and no expiry was seen. Conclusion: In summary, it can be concluded that the control of Diabetes Mellitus prevents patients from developing postoperative fatal complications.